2020
DOI: 10.3390/plants9091072
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Survey of MATE Transporters in Brassicaceae and Unveiling Their Expression Profiles under Abiotic Stress in Rapeseed

Abstract: The multidrug and toxic compound extrusion (MATE) protein family is important in the export of toxins and other substrates, but detailed information on this family in the Brassicaceae has not yet been reported compared to Arabidopsis thaliana. In this study, we identified 57, 124, 81, 85, 130, and 79 MATE genes in A. thaliana, Brassica napus, Brassica oleracea, Brassica rapa, Brassica juncea, and Brassica nigra, respectively, which were unevenly distributed on chromosomes owing to both tandem and segmental dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…For example, our CarMATEs count ( n = 48) is relatively low compared to that reported by Zhang et al (2020) , who identified 56 CarMATEs using the reference genome of the CDC Frontier available in the NCBI database (BioProject: PRJNA190909 ). At the same time, compared with previous studies, we identified comparable numbers of MATEs in the dicot model Arabidopsis ( Arabidopsis thaliana ; n = 57) and the monocot model rice ( Oryza sativa ; n = 55; Huang et al, 2019 ; Qiao et al, 2020 ), which further validates our identification strategy based on the MATE-domain based hmm profile search.…”
Section: Discussionsupporting
confidence: 81%
“…For example, our CarMATEs count ( n = 48) is relatively low compared to that reported by Zhang et al (2020) , who identified 56 CarMATEs using the reference genome of the CDC Frontier available in the NCBI database (BioProject: PRJNA190909 ). At the same time, compared with previous studies, we identified comparable numbers of MATEs in the dicot model Arabidopsis ( Arabidopsis thaliana ; n = 57) and the monocot model rice ( Oryza sativa ; n = 55; Huang et al, 2019 ; Qiao et al, 2020 ), which further validates our identification strategy based on the MATE-domain based hmm profile search.…”
Section: Discussionsupporting
confidence: 81%
“…In plants, they participate in diverse functions that regulate plant development and adaptation to stresses, by transporting and sequestering harmful substances and secondary metabolites. Although MATE genes have been identified in several plant genomes [50][51][52][53][54][55][56][57][58][59], little is known about the function of MATE transporters in Solanaceous species, which are of high economic and agronomic importance. Here, we performed a comprehensive genome-wide identification of MATE genes in pepper and potato, two members of the Solanaceae, identifying 42 CaMATE and 60 StMATE genes.…”
Section: Discussionmentioning
confidence: 99%
“…From the Leguminosae family in the eudicots, 70 were identified in M. truncatula [53], 117 in soybean [54], and 67 in pigeon pea (Cajanus cajan) [55]. In other eudicots, 71 were identified in poplar (Populus trichocarpa) [56], 73 in flax (Linum usitassimum) [57], 67 in Citrus sinensis [58], 56 in Arabidopsis [50], and 79-130 in four Brassicaceae species [59].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the ABC transporters, involvement of other transporters including multidrug and toxic compound extrusion (MATE) family proteins [ 189 , 190 ], zinc-iron permease ( ZIP) , iron-regulated transporters ( IRT1 ) [ 190 ], natural resistance-associated macrophage proteins (NRAMP), copper transporters (Ctr/COPT), and heavy metal ATPase (HMA) transporters [ 191 ] has also been highlighted in tolerance to HM toxicity. These metal transporters are involved in mediating metal intake and translocation in plants [ 192 ].…”
Section: Sequestration and Compartmentalization: Plants’ Way To Alleviate The Hm Toxicitymentioning
confidence: 99%